2023
DOI: 10.1108/ijieom-11-2022-0059
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of vibration in the multi-objective optimization of dry turning of hardened steel

Abstract: PurposeThis study aims to investigate the effect of vibration on ceramic tools under dry cutting conditions and find the optimum cutting condition for the hardened steel machining process in a computer numerical control (CNC) lathe machine.Design/methodology/approachIn this research, an integrated fuzzy TOPSIS-based Taguchi L9 optimization model has been applied for the multi-objective optimization (MOO) of the hard-turning responses. Additionally, the effect of vibration on the ceramic tool wear was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…An exact solution approach was utilized to solve the problem. Ahmed et al [24] suggested a novel humanitarian location-allocation-inventory model by focusing on preventing COVID-19 outbreaks with IoT-based technology in the response phase of disasters.…”
Section: Location and Allocationmentioning
confidence: 99%
See 1 more Smart Citation
“…An exact solution approach was utilized to solve the problem. Ahmed et al [24] suggested a novel humanitarian location-allocation-inventory model by focusing on preventing COVID-19 outbreaks with IoT-based technology in the response phase of disasters.…”
Section: Location and Allocationmentioning
confidence: 99%
“…Constraint (23) illustrates the maximum allowable distance between people at the demand point. Constraints (24) and ( 25) represent the types of variables used.…”
Section: Mathematical Modelmentioning
confidence: 99%